â€œLaskar Pelangiâ€ä¸æ–‡ç¿»è¯‘ç‰ˆã€Šå¤©è™¹æˆ˜é˜Ÿå°å¦ã€‹å°è¯´ä¸ä¿®è¾žæ ¼çš„æ–‡åŒ–éšå–» (The cultural metaphor of rhetoric in the novel "The Rainbow Team Primary School" as chinese translation version of "Laskar Pelangi") - Susi Susi; Yenny Yenny; Herman Herman (Jurnal Asosiasi Program Studi Mandarin Indonesia (Jurnal APSMI), 2022)
Â Â Â Â  æ‘˜è¦: ä¿®è¾žåœ¨æ–‡å¦ä½œå“æ‰®æ¼”é‡è¦è§’è‰²ã€‚ä¿®è¾žçš„è¿ç”¨ä¸ä½†ä½¿ä½œå“æ›´æœ‰è¶£è€Œä¸ä¹å‘³, è¿˜æé«˜ä½œå“çš„ç¾Žå¦ä»·å€¼èµ·ä½œç”¨ã€‚ã€Šå¤©è™¹æˆ˜é˜Ÿå°å¦ã€‹åŽŸåâ€œLaskar Pelangiâ€æ˜¯å°åº¦å°¼è¥¿äºšå›½å®‰å¾·çƒˆÂ·ä¼Šæ‹‰å¡”å†™å‡ºçš„ä¸€éƒ¨ä¼˜è¶Šçš„æ–‡å¦ä½œå“ï¼Œä¸ä»…åœ¨æœ¬åœ°æ–‡å¦ç•Œäº«æœ‰å¾ˆé«˜çš„å¨æœ›ä¹Ÿå—åˆ°å›½å¤–çš„æ³¨ç›®ã€‚æ¤å°è¯´çš„æ™®åŠæ€§ç”šå¹¿ï¼Œå› å·²è¢«ç¿»è¯‘æˆå„ç§å¤–è¯ï¼Œè€Œä¸æ–‡æ˜¯å…¶ä¸ä¹‹ä¸€ã€‚æœ¬æ–‡ä»¥è¯è¨€å¦ç†è®ºå’Œä¿®è¾žç†è®ºä¸ºç†è®ºåŸºç¡€ï¼Œé€šè¿‡å®šæ€§æ–‡çŒ®åˆ†æžæ³•æ¥ç ”ç©¶ã€Šå¤©è™¹æˆ˜é˜Ÿå°å¦ã€‹å°è¯´ä¸æ‰€è¿ç”¨çš„ä¿®è¾žæ ¼å¼ä»¥åŠæ‰€è•´å«çš„æ–‡åŒ–å†…å®¹ï¼Œé‡‡ç”¨è¯¥å°è¯´æ–‡çŒ®å½¢å¼ï¼Œæœ‰å…³ç ”ç©¶çš„å›¾ä¹¦ï¼Œè®ºæ–‡ç‰æ¥æ”¶é›†èµ„æ–™ã€‚æœ¬ç ”ç©¶çš„ç›®çš„æ˜¯åˆ†æžè¯¥ä¸æ–‡ç¿»è¯‘ç‰ˆå°è¯´ä¸æ±‰è¯ä¿®è¾žæ ¼çš„ä½¿ç”¨ï¼Œå¹¶æè¿°å…¶ä¸æ‰€è•´å«çš„æ–‡åŒ–éšå–»ã€‚ç ”ç©¶å‘çŽ°ï¼šè¯¥å°è¯´ä½¿ç”¨äº†24 ç§ä¿®è¾žæ ¼ï¼Œä½¿ç”¨ç‰¹è‰²ä¹‹å¤„åœ¨äºŽâ€œå¯¹æ¯”æ€§â€è¾žæ ¼å ä¸»å¯¼ï¼Œä»¥â€œæ˜Žå–»â€ä½œä¸ºä½œå“ä¸æœ€çªå‡ºçš„ä¿®è¾žæ ¼å¼ï¼Œæ¤å¤–ï¼Œå½“ä¸çš„6 ç§ä¿®è¾žå½¢å¼ï¼šå¼‚è¯ã€å¼•ç”¨ã€æ¯”å–»ã€æŽ’æ¯”ã€å å—å’Œæ¯”æ‹Ÿä¿®è¾žæ ¼å¼éšå–»äº†å°å°¼çš„æ–‡åŒ–ä»·å€¼ã€‚Â Â Â Â  å…³é”®è¯ï¼šå¤©è™¹æˆ˜é˜Ÿå°å¦ï¼›ä¿®è¾žæ ¼ï¼›æ–‡åŒ–éšå–»Â Â Â Â Â  Abstract: Rhetoric plays an important role in literature. The use of rhetoric not only makes the literature more interesting and not vapidity, but also enhances its aesthetic value. "The Rainbow Team Primary School" is the Chinese translated novel of "Laskar Pelangi", which is an excellent literary work written by Andrea Hirata from Indonesia. It not only enjoys high prestige in the local literary world, but also attracts attention from abroad. The popularity of this novel is so wide that it has been translated into various foreign languages, and Chinese is one of them. Based on linguistic theory and rhetoric theory, this article uses qualitative literature analysis to study the rhetorical format and cultural contained in the novel "The Rainbow Team Primary School", using the form of the novel literature, books and papers related to collect the research information. The purpose of this research is to analyze the use of Chinese rhetoric in the Chinese translated novel and describe the cultural metaphors contained in it. The research found that: The novel uses 24 types of rhetoric. The characteristic of the use is that the â€œcontrastiveâ€ rhetoric is dominant, and the â€œsimileâ€ is the most prominent rhetoric format in the literature. In addition, there are 6 rhetoric forms: foreign language , quotation, metaphor, parallelism, repetition, and metaphorical rhetoric format metaphors the cultural content of Indonesia.Â Â Â Â Â  Keywords:Â The Rainbow Team Primary School; Â Rhetoric; Cultural Metaphor